SIKAP HIDUP PERANAKAN TIONGHOA DALAM NOVEL CA BAU KAN KARYA REMY SYLADO - Sari Herleni (Balai Bahasa Provinsi Riau, 2017)
This study was based on the assumptions that every literary work is the picture of existing reality. This study was conducted to describe the existence of cultural social background in a literary work and to add the information about the society of Tionghoa descendence as part of Indonesian society. The method applied in this study was descriptive method by using literary sociological approach. The findings of this study showed that the Ca Bau Kan novel describe the life attitudes of Tionghoa descendence in general. The positive attitudes they had were (1) They appreciated time and money very much; and (2) They were good sport when they wanted to attack their enemies. On the other hand, the negative attitudes they had were (1) They would do everything to solve their problems; (2) They liked to “take care of” other women; and (3) They did not have high nationality in a country where they earn livelihood for life.